Analisis Faktor-Faktor yang Memengaruhi Loyalitas Konsumen pada Aplikasi GoFood - Ni Kadek Dwi Cahya Sri Andini; Putu Purnama Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of customer experience and discounts on customer satisfaction and customer loyalty, as well as the mediating role of customer satisfaction on the influence of customer experience and discounts on customer loyalty. The location of this study is Denpasar City and the sample used in this study is Generation Z in Denpasar City, with a total of 140 respondents. Data analysis techniques were carried out using SmartPLS 4. The results of the study indicate that customer experience has a positive and significant effect on customer loyalty, discounts have a positive and significant effect on customer loyalty, customer experience has a positive and significant effect on customer satisfaction, discounts have a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, the role of customer satisfaction as a mediating variable in the relationship between customer experience has a positive and significant effect on customer loyalty and the role of customer satisfaction as a mediating variable in the relationship between discounts has a positive and significant effect on customer loyalty. The suggestion that can be given by the researcher is that the GoFood Application management is expected to provide discounts on every purchase, provide an application that is comfortable to use, and can provide a fast response, and collaborate with more restaurants, innovate the design and appearance of the GoFood application so that it looks simpler and easier to use, provide discounts in a longer period of time and improve the quality of the service facilities provided.